Redefining a New Meaning of Thai Temples in Contemporary Society: A Case Study of Wat Phuket, Nan Province - Angasinha, Asisst. Prof. Dr. Chatwarun; Bunmenimit, Oranee (Journal of Dhamma for Life, 2023)
This research is a qualitative study with the objective of presenting new meanings and new management approaches for Thai temples and their surrounding communities to promote contemporary relevance. The study found that Wat Phuket in Pua District, Nan Province, has created new meanings in its role as a religious tourism destination through the process of rebranding. This includes the establishment of a temple stay program and a community-involved tourism management process that fosters positive relationships between the temple, the community, and local residents. As a result, the community has strengthened economically, socially, and environmentally. The process of rebranding Wat Phuket as a religious tourism destination is not only a cognitive shift but also a means of creating opportunities by opening intellectual and social spaces for collective thinking and creation by community members. This has evolved into a social innovation that empowers the Ban Ked community, arising from the interplay of structure, agency, and actors. It continuously reproduces actions that maintain the new meaning of the temple, and it has demonstrated a change in the development approach, characterized by collective action by the temple and the community, aimed at sustainability in contemporary society.